Mosaic Structure Characterization of the AlInN Layer Grown on Sapphire Substrate. (10th August 2014) - Arslan, Engin; Demirel, Pakize; Çakmak, Huseyin; Öztürk, Mustafa K.; Ozbay, Ekmel
Abstract : The 150 nm thick, (0001) orientated wurtzite-phase Al1− x In x N epitaxial layers were grown by metal organic chemical vapor deposition on GaN (2.3  µ m) template/(0001) sapphire substrate. The indium ( x ) concentration of the Al1− x In x N epitaxial layers was changed as 0.04, 0.18, 0.20, 0.47, and 0.48. The Indium content ( x ), lattice parameters, and strain values in the AlInN layers were calculated from the reciprocal lattice mapping around symmetric (0002) and asymmetric (10–15) reflection of the AlInN and GaN layers. The mosaic structure characteristics of the AlInN layers, such as lateral and vertical coherence lengths, tilt and twist angle, heterogeneous strain, and dislocation densities (edge and screw type dislocations) of the AlInN epilayers, were investigated by using high-resolution X-ray diffraction measurements and with a combination of Williamson-Hall plot and the fitting of twist angles.